ChemInform Abstract: Functionalized Carbodiimide Mediated Synthesis of 2, 3‐Disubstituted Quinazolin‐4(3H)‐ones via the Tandem Strategy of C‐Nucleophilic Addition and Intramolecular NH‐Substitution Cyclization. Issue 6 (20th February 2013) - Nakano, Hayato; Kutsumura, Noriki; Saito, Takao
Abstract An aza‐Wittig reaction of iminophosphorane (I) with isocyanates (II) forms carbodiimides which are coupled as crude products with various organometallic reagents to give access to a broad spectrum of fused pyrimidine structures.